60.5k views
0 votes
Multiply.

(4x+2)(3x+3)

User AndVla
by
5.3k points

2 Answers

2 votes

Answer:


\boxed{12 {x}^(2) + 18x + 6}

Explanation:


= > (4x + 2)(3x + 3) \\ \\ = > 4x(3x + 3) + 2(3x + 3) \\ \\ = > (4x * 3x) + (4x * 3) + (2 * 3x) + (2 * 3) \\ \\ = > 12 {x}^(2) + 12x + 6x + 6 \\ \\ = > 12 {x}^(2) + 18x + 6

User Froblesmartin
by
4.5k points
6 votes

The right answer is 12x^2+18x+6

please see the attached picture for full solution

Hope it helps

Good luck on your assignment

Multiply. (4x+2)(3x+3)-example-1
User Raychel
by
5.5k points